Total Synthesis of Benthol A: Evidence for a Structure Revision - Guanghao Huang; Andrea Tomio; Thomas Varlet; Conny Wirtz; Alois Fürstner (Journal of the American Chemical Society, 2026)
Abstract Benthol A, a dinoflagellate-derived polyol/polyether marine natural product endowed with potent antimalaria and appreciable antiviral activity, consists of a 72 C atom linear backbone featuring 35 stereogenic centers and four stereogenic alkenes. The constitution and configuration of this intriguing “super-carbon-chain compound” had been assigned by the isolation team by a combination of spectroscopic, chemical, and computational means. Outlined in this and the accompanying paper is the first total synthesis of this challenging target, which came along with a subtle structure revision. During the synthesis of the building blocks, a spectral irregularity was noticed in that the 13C NMR chemical shifts as well as some of the 3JH,H coupling constants of the synthetic samples deviated notably from the data reported for the entire C31–C41 region of benthol A corresponding to the tetrahydropyran E-ring and its vicinity. A systematic approach made it possible to narrow down the likely site of error to a single, incorrectly assigned stereocenter, i.e., the C40 position; interestingly, the configuration of this site had been determined by the isolation team solely by computational means. In chemical terms, our studies showed how the proper choice of a propargylic protecting group allows the regiochemical course of a gold-catalyzed spiroacetalization reaction to be steered. Moreover, carbonyl homologation by the addition of a highly functionalized but entirely unstabilized diazo derivative generated in situ to an equally highly functionalized aldehyde proved adequate for the coupling of elaborate building blocks (Buchner–Curtius–Schlotterbeck reaction).